UTILIZING BANDURA'S SOCIAL COGNITIVE THEORY IN ENTERTAINMENT-EDUCATION COMMUNICATION DESIGN: A CONCEPTUAL REVIEW - Medo Maulianza; Sarwititi Sarwoprasodjo; Nur Asni Gani (Multidisciplinary Research Studies in Social Sciences, 2026)
This review is motivated by the complex problems of development and the urgency of effective communication interventions to encourage behavioral change in society. Although edutainment has proven to be a promising communication strategy, there are theoretical, empirical, and practical gaps in its application in Indonesia, often without critical testing of the theory's assumptions and boundary conditions. This paper aims to map the assumptions, key concepts, and propositions of Albert Bandura's Social Cognitive Theory; identify its historical-paradigmatic roots; critically analyze the coherence, hidden assumptions, biases, and boundary conditions of the theory; synthesize empirical evidence from at least three Scopus-indexed articles applying SCT to relevant issues; compare SCT with the Diffusion of Innovations Theory; and test its relevance in real cases in Indonesia. The method used is a narrative-systematic literature review with specific inclusion criteria for Scopus articles. Key findings indicate that SCT excels in explaining individual psychological mechanisms in behavioral change through modeling and self-efficacy, which are highly relevant for edutainment design. However, SCT has limitations in explaining structural barriers or deeply ingrained social norms. The integration of SCT with the Diffusion of Innovations Theory is proposed for a more comprehensive framework.Keywords: Social Cognitive Theory, Albert Bandura, Edutainment, Development Communication, Behavior Change, Self-Efficacy